Salat Sahun dalam Al-Qur’an : Studi Komparatif Penafsiran Al-Qurthubi dan Sayyid Qutb atas Surah Al-Maun ayat 4-5 - Maulidatur Rofiqoh (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2022)
One of the central themes of the Qur'an is worship. It is one of the pillars of Islam that is most widely mentioned in the Qur'an, which it shows that prayer is one of the pillars of Islam that has an important role and function in the lives of Muslims. Therefore negligence (s?h?n) in prayer is prohibited, a person in establishing prayer is required to always remember that he is praying. The focus of this paper then is on the interpretation of surah al-M?’?n  (107): 4-5 about negligence in prayer in the eyes of al Qurtubi and Sayyid Qutb. This type of research uses library research and the method used is comparative analysis, by analyzing and comparing the interpretation of Al-Jami' li Ahkam al-Qur'an and the interpretation of fi Zilal al-Qur'an. The results show that in terms of the meaning of s?h?n is relatively same, both mufassir interpret equally that the meaning of s?h?n is negligence (not focused on praying). This is because they only pray with the aim of riya'. The difference between the two interpretations is that al-Qurthubi prefers to deal with it in the context of its implementation, such as praying outside the time limit, wasting prayer and even leaving prayer. Meanwhile, Sayyid Qutbin interpreting of surah al-M?’?n  (107): 4-5, is more revealing in the spirit of the verse by prioritizing the problems of society to be solved through the al-Qur’an, namely the implications of praying s?h?n on human behaviour.